2010
DOI: 10.1002/pen.21724
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanotalc inclusion on mechanical, microstructural, melt shear rheological, and crystallization behavior of polyamide 6‐based binary and ternary nanocomposites

Abstract: The objective of the study is to investigate the effect of inclusion of nanotalc on the strength properties of polyamide 6 (PA6)‐based binary and ternary nanocomposites. Binary nanocomposites were prepared by melt compounding of PA6 with varying content of nanotalc (1, 2, and 4 wt%). Ternary nanocomposites were prepared by melt compounding of compatibilized blend of PA 6 and ethylene‐co‐butyl acrylate (EBA elastomer) with varying content of nanotalc (1, 2, and 4 wt%). Both the binary and ternary nanocomposites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…4, 5), an increase of a second peak related to the increase of the SSMMP content can be seen. This behavior is probably due to the formation of a network structure by the surface hydroxyl groups of the nanofiller through hydrogen bonding with the polymeric chain as described in literature [10]. Indeed, the amount of hydroxyl groups present at the SSMMP layer edges increases with the increase of the specific surface area [7].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…4, 5), an increase of a second peak related to the increase of the SSMMP content can be seen. This behavior is probably due to the formation of a network structure by the surface hydroxyl groups of the nanofiller through hydrogen bonding with the polymeric chain as described in literature [10]. Indeed, the amount of hydroxyl groups present at the SSMMP layer edges increases with the increase of the specific surface area [7].…”
Section: Resultsmentioning
confidence: 86%
“…Natural talc is difficult to disperse in water and considered to be hydrophobic and more compatible with polymer matrix; it has been widely used as an effective filler in polymer, such as polyethylene [9], polyamide [8,10], polylactide [11], polyurethane [12], PU/PP blends [13,14], poly(lactic acid) [15,16] composites, to improve their properties. Especially, there are many researches on the effect of talc on the mechanical properties, thermostability, crystallizability and rheology of polypropylene/talc composites [8,[17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The usage of small talc particles has been studied in different applications, including reinforcement of thermoplastic starch films [7], food packaging bags [9], binary and ternary nanocomposites [10,11], and semi-crystalline plastics [12]. The smaller size of talc particles has been found to provide better properties for all these applications.…”
Section: Introductionmentioning
confidence: 98%
“…The effect of nanotalc on binary PA6/talc and ternary PA6/ethylene butyl acrylate (EBA)-g-MA/EBA/talc nanocomposites was investigated by Balamurugan and Maiti. 49 It is observed that binary and ternary nanocomposites registered high improvement in the stiffness/strength related properties at lower nanotalc content of 1 wt %. The improvement in strength related properties is due to the retention of high aspect ratio of nanotalc and ability of nanotalc particles to orient along the melt flow direction in the nanocomposites.…”
Section: Introductionmentioning
confidence: 91%
“…The effect of nanotalc on binary PA6/talc and ternary PA6/ethylene butyl acrylate (EBA)‐ g ‐MA/EBA/talc nanocomposites was investigated by Balamurugan and Maiti . It is observed that binary and ternary nanocomposites registered high improvement in the stiffness/strength related properties at lower nanotalc content of 1 wt %.…”
Section: Introductionmentioning
confidence: 99%